Impacts of heater-cooler position and Lorentz force on heat transfer and entropy generation of hybrid nanofluid convection in quarter-circular cavity - Manna, Nirmal K.; Biswas, Nirmalendu; Mandal, Dipak Kumar; Sarkar, U. K.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Emerald Group Publishing Ltd, 2023)
PurposeThe study aims to assess the heater and cooler positional impacts systematically using four different quadrantal cavities filled with hybrid nanofluid, keeping the curved surface adiabatic under the orientated magnetic fields. Both heat transfer and entropy generation analyses are performed for a hybrid nanofluid flow in a quarter circular cavity considering different orientations of magnetic fields. The investigation is focused to assess the heater and cooler positional impacts systematically using four different quadrantal cavities (first to fourth quadrantal cavities), keeping the curved surface always adiabatic. The impacts of pertinent variables like Rayleigh number, Hartmann number and volumetric concentration of hybrid nanofluid on heat transfer characteristics are in consideration with the second law of thermodynamics. The analysis includes the thermal, viscous and magnetic aspects of entropy generation. Design/methodology/approachAfter validating against the experimental results, the present work explores numerically following the Galerkin weighted finite element technique. The solution is obtained through an iterative process satisfying the convergence limit of 10(-8) and 10(-10) for the maximum residuals and the mass defect, respectively. FindingsIt revealed that the mutual exchange of heater-cooler positions on the adjacent straight edges of the quadrant cavity does not have any impact on the flow direction. Although the magnitude of flow velocity enhances, the sidewall plays a decision-making role in the formation of a single circulation vortex. It also shows that thermal entropy production is the main cause behind thermodynamic irreversibility. The second or third quadrantal arrangement could have been opted as the best configuration of the heater-cooler position for achieving superior heat transfer. The Lorentz force plays a great role to moderate the heat transfer process. The maximum entropy generation is located, as expected, at the heating-cooling junction point. Research limitations/implicationsThere are plenty of prospects for extension of the present research concept numerically or experimentally, adopting three-dimensional analysis, working fluids, boundary conditions, etc. In fact, the study could be carried out for unsteady or turbulent fluid flow. Practical implicationsAs the position of the heated source and cold sink on the enclosure geometry can significantly alter the thermo-fluid phenomena, this kind of analysis is of utmost relevance for the further development of efficient heating/cooling arrangements and proper management of the devices subjected to magnetic field applications. This original contribution could be a potentially valuable source for future research and exploration pertaining to a thermal system or device, like heat exchangers, solar collectors, thermal storage, electronic cooling, food and drying technologies and others. Originality/valueIn the literature, an inadequate number of works have focused on a quadrantal cavity, mostly considering the first quadrant of the circle. However, during practical applications, it is possible that the cavity can take the shape of the other three quadrants too, and the corresponding knowledge on relative performance is still missing. Furthermore, the present investigation includes the existence of magnetic fields at various orientations. The impact analysis of this field-induced Lorentz force on the nanofluid thermal performance is another major contribution from the present work that would enrich the domain knowledge and could be useful for thermal system engineers.
Keywords: Magnetic field; Nanoparticles; Heat transfer; Irreversibility; Quadrantal cavity